Study of Retro Cochlear Pathology for Finding Hearing Ability using Tone Decay Test (Global Journal of Medical Research, 2017)
Pure tone Audiometry (PTA)-Tone Decay Test is the key hearing test used to identify hearing threshold levels of an individual, enabling determination of the degree, type and configuration of a hearing loss. The test is used to indentify quickly screening for Retro Cochlear pathology. In audio logical investigations, the hearing sensitivity is tested for pure tones. The test tones of different frequencies and levels are generated and presented to the patient and hearing thresholds are determined on the basis of patient's response. Thus in this work we described the auditory system and its disorders.
Keywords: audiometer; pure tone decay